Exploring The Impact of TikTok Teleprompter Challenge on English Language Learners’ Confidence and Speaking Skills - Shakira Amalia; Chusnul Chotimah; Enci Zarkasih (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to explore the impact of the TikTok Teleprompter Reading study examines the impact of the TikTok Teleprompter Reading Challenge on the confidence and speaking abilities of English language learners. Using a qualitative case study design, data were collected through an online open-ended questionnaire from ten participants who had actively participated in reading challenges on TikTok. Six major themes emerged: Enjoyment and Engagement, Developing Confidence, Improving Speaking Skills, Difficulties Faced, Comparison with Traditional Learning, and Advice for Other Learners. The findings indicate that the short video format and scrolling text reduce psychological barriers to speaking, enhance fluency and pronunciation through repetitive practice, and build intrinsic confidence in a pressure-free environment. This research highlights how informal digital learning platforms can enhance learners' well-being and language proficiency, underscoring the powerful interplay between technology, enjoyment, and language acquisition.